Structural Variation of Element and Human Disease - Songmi Kim; Chun-Sung Cho; Kyudong Han; Jungnam Lee (Genomics & Informatics)
Transposable elements are one of major sources to cause genomic instability through various mechanisms including de novo insertion, insertion-mediated genomic deletion, and recombination-associated genomic deletion. Among them is Alu element which is the most abundant element, composing ~10% of the human genome. The element emerged in the primate genome 65 million years ago and has since propagated successfully in the human and non-human primate genomes. Alu element is a non-autonomous retrotransposon and therefore retrotransposed using L1-enzyme machinery. The 'master gene' model has been generally accepted to explain Alu element amplification in primate genomes. According to the model, different subfamilies of Alu elements are created by mutations on the master gene and most Alu elements are amplified from the hyperactive master genes. Alu element is frequently involved in genomic rearrangements in the human genome due to its abundance and sequence identity between them. The genomic rearrangements caused by Alu elements could lead to genetic disorders such as hereditary disease, blood disorder, and neurological disorder. In fact, Alu elements are associated with approximately 0.1% of human genetic disorders. The first part of this review discusses mechanisms of Alu amplification and diversity among different Alu subfamilies. The second part discusses the particular role of Alu elements in generating genomic rearrangements as well as human genetic disorders.